Community Service: Communication in Digital Era: Business Presentations and Their Relevance in the Workplace - Vinny Stephanie Hidayat; Verani Carolina; Rini Handayani; Herman Kambono; I Nyoman Agus Wijaya; Sinta Setiana; Kwang En Tan; Vicky Putra Surifran (Jurnal Pengabdian Pada Masyarakat, 2023)
For GJKI Andir Bandung members, a community service event with the topic "Communication in Digital Era" was held on October 14, 2023, and 60 people attended. This community service project aims to improve the younger generation's comprehension of business communication and how to deliver business presentations effectively in front of an audience. "Speak Up: Changing the World By Talking" was the title of the presentational material. Counseling, group business communication exercises, business presentation exercises, conversations, and question-and-answer sessions are all used to carry out this activity. After taking part in this service activity, it can be said that the participants have a better understanding of the concept of business communication and can make straightforward business presentations.